2007
DOI: 10.1007/s10562-007-9045-5
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Al2O3 support on the activity of Ag/Al2O3 catalysts for SCR of NO with decane

Abstract: The role of the Al 2 O 3 support on the activity of supported Ag catalyst towards the selective catalytic reduction (SCR) of NO with decane is elucidated. A series of Ag/Al 2 O 3 catalysts were prepared by impregnation method and characterized by N 2 pore size distribution, XRD, UV-Vis, in-situ FT-IR and acidity measurement by NH 3 and pyridine adsorption. The catalytic activity differences of Ag/Al 2 O 3 are correlated with different properties of Al 2 O 3 supports and the active Ag species formed. 4wt% Ag su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 27 publications
0
26
0
Order By: Relevance
“…The following parameters were used to collect data: 800-200 nm measurement range and 200 nm/min scanning speed. The measured spectra were converted into Kubelka-Munk functions and deconvoluted into Gaussian subbands that could be quantitatively assigned to the different Ag species [12,[18][19][20][21].…”
Section: Catalyst Characterizationmentioning
confidence: 99%
“…The following parameters were used to collect data: 800-200 nm measurement range and 200 nm/min scanning speed. The measured spectra were converted into Kubelka-Munk functions and deconvoluted into Gaussian subbands that could be quantitatively assigned to the different Ag species [12,[18][19][20][21].…”
Section: Catalyst Characterizationmentioning
confidence: 99%
“…There are many species (spectra not shown) formed on the addition of H 2 over both catalysts. Below 2000 cm −1 , nitrates (1302 cm −1 ), formates (1393 and 1377 cm −1 ), acetates (1460 cm −1 ), and carboxylates (1589 cm −1 ) are observed [15,22,23,31,32,[34][35][36][37][38]43]. In addition, bands appearing between 2886 and 3000 cm −1 are associated with CH 3 and CH 2 stretching vibrations of hydrocarbon species [13,22,23,31,32,43].…”
Section: H 2 Switching With H 2 Omentioning
confidence: 98%
“…Silver-based catalysts are one of the most promising and cost effective systems for NO x HC-SCR but are relatively inactive at temperatures below 300 • C [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]. Various modifications to the standard wet impregnation preparation technique have been G Model CATTOD-9316; No.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, materials prepared by different methods resulted in different adsorption capacities of NO, water, and so on, leading to different catalytic performances [26]. It was also reported that the surface acidity contributed from the sol-gel improved hydrocarbon activation and NO conversion [27].…”
Section: Preparation Effectmentioning
confidence: 99%